GEOLOGICAL-STRUCTURAL MODEL OF FORMING OF THE GOLD ORE DEPOSIT OF SOTSK (Proceedings of the YSU C: Geological and Geographical Sciences, 2003)
The ore-enclosing rocks of the Sotsk deposit are subject to metamorphic and metasomatic processing. The separate ore bodies with depth combine in one (stock). The main parts of mineralization is timed to extreme parts of gabbro and peridotites, which are distinguished by their petrophysical parameters. The character of gold mineralization distribution testifies, that upper part of deposit is most perspective. The stage of intensive mineralization is distinguished, the mineralization fades with depth. The hard foundation, located at the short depth, is broken up by tectonic breaches which were favourable surroundings for penetration of hydrothermal solution.
Keywords: Sotsk deposit; metamorphic and metasomatic processing; gabbro and peridotites; petrophysical parameters; Republic of Armenia